A radical change of heart: Robert Wedderburn’s last word on slavery - Hanley, R (Routledge, 2015)
This article introduces to modern scholarship An Address to Lord Brougham and Vaux, a recently rediscovered anti-abolitionist tract by the black radical author and orator Robert Wedderburn, written in 1831, towards the end of his life. It gives a brief biography of the author and introduces some of the key themes that characterised his earlier work. Questions of authenticity and authority are raised in the context of earlier appropriations of Wedderburn’s already fluid authorial identity and the specific social and political circumstances surrounding the text’s publication. A transcript of the text is provided with some minor elisions.